Kebijakan Kepala Sekolah Dalam Peningkatan Kompetensi Pedagogik Guru Di Mts Tarbiyatul Mubtadi’in Bekasi - Idham; Ilyas Mukti Wibowo (Edukasiana: Journal of Islamic Education, 2023)
ABSTRACT An educational institution has a principal who implements policies to improve teachers' pedagogical competence. School success is not only determined by physical facilities, but also by the policies implemented by the principal. formal educational institution that seeks to improve teachers' pedagogical competence, especially in effective learning management. This study aims to identify the principal's policy, its implementation, the support provided, and the evaluation that can improve teachers' pedagogical competence. The research method used was descriptive qualitative research with data collection through observation, interviews, and documentation involving the principal, vice principal, teachers, and students as resource persons. The results showed that principals conduct various policies such as lesson preparation, training and teacher performance assessment. They also encourage mentoring, create a positive work environment, and open opportunities for teachers to develop by equipping facilities at school. Evaluation is also an important component in the effort to improve teachers' pedagogical competence by providing space for teachers to provide feedback and criticism.. Keywords: Principal Policy, Pedagogical Competence.